Inside the Texas Revolution : The Enigmatic Memoir of Herman Ehrenberg - Ehrenberg, Herman, 1816-1866 (Book collections on Project MUSE., 2021)
"Herman Ehrenberg wrote the longest, most complete, and most vivid memoir of any soldier in the Texan revolutionary army"--